Improved method using a two Exclusive-OR to binary image in RGB color image steganography - Mohammed Farhan, Hamid; Ahmed Alwan, Zena (International Journal of Engineering and Technology, 2018)
In this paper present adaptive technique algorithm to hide the secret Binary image inside color image to make information of binary image more save omit we used steganography technique was Least Significant Bit(LSB). We are applying Two Exclusive-OR operations between our secret Binary Image and 8-bit (Red, Green, and Blue) bands in color Image. We are hiding our secret encrypted Binary Image in the LSB of Blue bands. Each pixel will have applying Two XOR operations sequential to increases security to the Binary Image, and then store our encrypted pixel in 8-bit-LSB of Blue band, the stored data at this place is not the real data but it obtains by performing the Exclusive-OR operation. This method applied to different set of images. Furthermore, it observed that the projected method assure good result as the "Peak Signal to Noise Ratio (PSNR)" and "stands for Mean Square Error (MSE)" are good. When the method compared with other existing methods, it shows enhancement in the imperceptibility and message capacity. This method was easy to make, easy to understand and provide security against attack.Â Â Â
Keywords: Image Security; Information Hiding; LSB; Steganography; Exclusive-OR Operation.